2017
DOI: 10.1021/acs.jpcb.7b05296
|View full text |Cite
|
Sign up to set email alerts
|

Materials Screening for the Discovery of New Half-Heuslers: Machine Learning versus ab Initio Methods

Abstract: Machine learning (ML) is increasingly becoming a helpful tool in the search for novel functional compounds. Here we use classification via random forests to predict the stability of half-Heusler (HH) compounds, using only experimentally reported compounds as a training set. Cross-validation yields an excellent agreement between the fraction of compounds classified as stable and the actual fraction of truly stable compounds in the ICSD. The ML model is then employed to screen 71,178 different 1:1:1 compositions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 31 publications
(87 reference statements)
0
73
0
Order By: Relevance
“…Here, we will review ML works aimed at specifically identifying thermoelectrics through property predictions. There are several works that aim to identify new intermetallic structures (e.g., Heuslers being a major class) and their stability, but make no attempt to predict other critical thermoelectric properties . These works will not be reviewed here.…”
Section: Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we will review ML works aimed at specifically identifying thermoelectrics through property predictions. There are several works that aim to identify new intermetallic structures (e.g., Heuslers being a major class) and their stability, but make no attempt to predict other critical thermoelectric properties . These works will not be reviewed here.…”
Section: Applicationmentioning
confidence: 99%
“…There are several works that aim to identify new intermetallic structures (e.g., Heuslers being a major class) and their stability, but make no attempt to predict other critical thermoelectric properties. [117,299,300] These works will not be reviewed here.…”
Section: Thermoelectricsmentioning
confidence: 99%
“…Many classification and regression algorithms can be applied to predict the chemical composition of a material from its structure . Perovskite is an important crystal structure in many fields .…”
Section: Applicationsmentioning
confidence: 99%
“…This model realized a high true‐positive rate of .94 and successfully predicted 12 novel gallides, namely, MRu 2 Ga and RuM 2 Ga (M = Ti − Co), as Heusler compounds. Legrain et al trained a model using experimentally reported compounds to predict the stability of half‐Heusler compounds. The model, which was based on the random forest algorithm, retrieved 71 178 compositions and yielded 30 results, which mostly matched half‐Heusler compounds, for further exploration.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation